Bridging Policy and Practice: How Kindergarten Principals Manage Inclusive Education in Resource-Constrained Environments - Barokatin, Roina; Sukinah, Sukinah (Papanda Publisher, 2025)
Inclusive education in early childhood settings requires effective principal leadership, yet empirical evidence on management strategies in developing contexts remains limited. This study examined how a kindergarten principal manages inclusive education in a multicultural, resource-constrained environment. A qualitative case study was conducted at YPPSB Kindergarten, East Kutai, Indonesia, from January to June 2025. Data were collected through in-depth interviews with the principal, teachers, special education teachers, and parents, complemented by participant observation and document analysis. Data were analyzed using Miles, Huberman, and Saldaña's interactive model. Findings revealed that the principal implemented comprehensive strategies across three dimensions: (1) participatory planning involving multi-stakeholder collaboration and individualized education plan development, (2) collaborative implementation through co-teaching models and differentiated instruction, and (3) systematic sustainability mechanisms including institutionalized inclusion teams, strategic external partnerships, and diversified funding. The principal integrated local cultural values into inclusive practices while establishing formal structures ensuring program continuity. These strategies exemplify transformational and distributed leadership principles, extending inclusive education scholarship into early childhood contexts. The study demonstrates how principals can leverage community partnerships and cultural resources to address implementation challenges in resource-constrained settings, bridging the documented policy-practice gap in inclusive education.